Pengaruh Penggunaan Model Pembelajaran Sinektik Terhadap Kemampuan Menulis Puisi Siswa Kelas V Di SD Negeri 49 Kota Bengkulu - Hamidah Hamidah; Resnani Resnani; Lukman Lukman (JURIDIKDAS, 2019)
This study aims to determine the effect of the use of synoptic learning model on the ability to write poetry of class V students in SD Negeri 49 Kota Bengkulu. The type of this research is quantitative research and the research design is The Matching Only Pretest-Posttest Control Group Design, taking the test twice before and after giving treatment (treatment) in the sample class. Population in this research is class V student amounted to 43 student. The sample in this research consists of two classes, namely VB as experimental class and VA as control class with sampling total sampling technique. The research instrument uses a description test (essay). The data of the research were analyzed using inferential analysis that is t-test. Based on the results of data analysis obtained tcount value of 2.39 and ttable value of 2.019 with a significant level of 5%. This shows that the tcount = 2.39 ? ttable = 2.019 and it is concluded that there is an effect of using a synoptic learning model on the ability to write poetry of class V students in SD Negeri 49 Kota Bengkulu.